A flexible remote laboratory with programmable device under test. (May 2020) - Angrisani, Leopoldo; Bonavolontà, Francesco; D'Arco, Mauro; Liccardo, Annalisa
Highlights: Remote Laboratory for education in Measurements and Instrumentation. Board FPAA to modify the analog circuit involved in the experiments. Assessment of laboratory response time and management of concurrences. Survey for assessing the laboratory effectiveness. Abstract: Experimental practice in laboratory is a fundamental teaching issue in electrical and electronic measurement courses. Unfortunately, crowded classes, along with limited universities resources, do not allow to meet this need through actual laboratory sessions. In such a context, remote laboratories have proved to be an excellent solution. A significant added value, in a remote laboratory, is the possibility to modify the test circuit, in order to vary the type of experiment. The authors suggest, in the paper, to overcome t he considered limitations by integrating inside the remote laboratory suitable devices that can be remotely configured, i.e. a Field Programmable Analog Array (FPAA). FPAA is exploited for emulating the behavior of a large variety of analog circuits, thus making it possible for users, either students or technicians, to select the desired test circuit and carry out the experiment from home.